The Relationship Between Learning Motivation and Learning Outcomes for Midwifery Care Courses for Third Semester Students at STIKes Senior Medan's Midwifery Study Program - Faradita Wahyuni; Esther Siringo-Ringo; Mastiur Julianti Butar-Butar; Indah Yani Tambunan (International Archives of Medical Sciences and Public Health, 2022)
Changes in the learning process are required to improve the quality of education in Indonesia. The motivation to learn is one of the factors that determines a student's success or failure in the learning process. The goal of this study was to discover the relationship between Learning Motivation and Learning Outcomes of the Midwifery Care II Course in Prodi S-1 Kebidanan STIKes Senior Medan. This study's research design is an analytical survey with a cross-sectional approach. Using the total population sampling technique, the population is taken from as many as 58 students in the fourth semester of Prodi S-1 Kebidanan STIKes Senior Medan. According to the results of an analysis using the statistical test chi-square, the majority of students (44.8%) have enough motivation. According to the learning results, the majority of students get good learning results, as many as 31 people (53,4%) and found Asymp Sig value (0,008 0,05). Students who are still unmotivated to learn must be improved in order to achieve the goals and desire to achieve good learning outcomes.